Influence of carbon doping and hydrogen co-doping on acceptor related optical transitions in ZnO nanowires. (24th March 2017) - Mohammadbeigi, F; Kure, T; Callsen, G; Kumar, E Senthil; Wagner, M R; Hoffmann, A; Watkins, S P
Abstract: ZnO nanowires grown by metalorganic vapor phase epitaxy in the presence of carbon tetrachloride and hydrogen show two distinct low temperature photoluminescence (PL) bands at 3.237 and 3.309 eV. The band at 3.237 eV is most pronounced in samples grown in the presence of carbon tetrachloride, and is shown to be due to donor–acceptor pair (DAP) emission, based on intensity-dependent and time-resolved PL measurements. An acceptor binding energy of 181 ± 5 meV was inferred from these measurements. We attribute the acceptor in this DAP to the incorporation of nitrogen due to interaction between the carbon and nitrogen precursors. The addition of hydrogen in the presence of CCl4 results in a large enhancement of the carbon related shallow donor bound exciton PL, and the appearance of a strong band at 3.309 eV (e–A 0 ) which is consistent with a free-to-bound transition, most likely (e–A 0 ) as argued by previous works. The (e–A 0 ) designation is based on detailed lineshape analysis as a function of temperature, together with time-resolved PL measurements. Based on this model, an acceptor binding energy for the 3.309 eV band of 133 ± 5 meV was determined, confirming and supporting previous reports.